2013
DOI: 10.1007/s11524-013-9801-3
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need for Medical Care and Safety Net Accessibility among Birmingham’s Homeless

Abstract: Although homeless individuals often experience health problems requiring care, there are limitations to available research concerning the scale of their needs and the accessibility of safety net agencies to meet them. Traditional access-to-care surveys calculate unmet need among all persons queried (rather than persons needing care), making it difficult to calculate what percentage of persons requiring care actually obtain it. Additionally, no research has compared the relative accessibility of safety net prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 23 publications
(23 reference statements)
0
55
0
1
Order By: Relevance
“…25 Homeless Hispanic women were also more likely to have a usual source of care than White homeless women. 25 When examining unmet needs, Kertesz et al 19 concluded that Black homeless persons were less likely to report unmet needs for general medical care compared to White homeless persons (OR = 0.38; 95% CI = 0.17-0.85). Kushel et al 2 found substance abuse to be associated with increased primary care access.…”
Section: Characteristics Of the Homelessmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Homeless Hispanic women were also more likely to have a usual source of care than White homeless women. 25 When examining unmet needs, Kertesz et al 19 concluded that Black homeless persons were less likely to report unmet needs for general medical care compared to White homeless persons (OR = 0.38; 95% CI = 0.17-0.85). Kushel et al 2 found substance abuse to be associated with increased primary care access.…”
Section: Characteristics Of the Homelessmentioning
confidence: 99%
“…19 In the survey, 86% of participants reported the inability to pay for care as a common barrier to obtaining health services. While having long wait times, free clinics provided gratis care and had less restrictive requirements when compared with county hospital clinics and EDs.…”
Section: Utilization Of Health Servicesmentioning
confidence: 99%
“…5 In another report, an estimated 38 % of homeless patients had more than one chronic medical condition compared to only 27 % of their peers, and over half of homeless healthcare seekers have described unmet medical needs. 6,7 Homeless individuals also face a confluence of particular barriers, including competing sustenance needs, environmental stress (weather, violence, infections, trauma), and few social supports. 8,9 The literature has highlighted the cumulative and continued impact of these risk factors even when homeless individuals achieve housing.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The literature has highlighted the cumulative and continued impact of these risk factors even when homeless individuals achieve housing. 7,10,11 Diabetes mellitus is one example of a chronic medical condition where unmet healthcare needs may impact health outcomes. Type 2 diabetes affects nearly 26 million people in the United States, or 8.3 % of the U.S. population.…”
Section: Introductionmentioning
confidence: 99%
“…Across the nation, physical and mental healthcare needs have been documented among homeless adults (Brown, Kiely, Bharel, & Mitchell, 2012; Garibaldi, Conde-Martel, & O'Toole, 2005; Kertesz et al, 2013). In particular, addiction, mental illness, hypertension, and diabetes are significant issues among those experiencing homelessness (Kertesz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%